Pen sanitizer / Sri Yogambigai Ananthan ... [et al.] - Ananthan, Sri Yogambigai; Million, Hemalekka; Krishnan, Keerthana; Neru, Thilagan; Million, Sandiya; Paneerselvom, Muniandy; Tivaraju, Jemima (Universiti Teknologi MARA, Perak, 2020)
Coronavirus (covid-19) is an infectious disease caused by a newly discovered virus from the state of Wuhan in China. This pandemic virus is killing millions of people all over the world. Most people infected with the covid-19 virus will experience mild to moderate respiratory illness and recover without requiring special treatment. Older people, and those who have underlying medical problems like cardiovascular disease, diabetes, chronic respiratory disease and cancer patients are more likely to face their death in a couple of weeks. The best way to prevent and slow down the transmission is to protect yourselves and others by washing your hands frequently by using hand sanitizer or soapy water by not touching your senses. In overcoming this serious issue we have invented pen-sanitizer to protect us from the social context. This pen-sanitizer can be known as the most effective way in our daily routine especially in offices, banks, schools and in most social signing places. It will help protect us from stop sharing the pen being placed in social places. By using the newly invented pen-sanitizer we can frequently sanitize our hand by not waiting too long just to get a pinch of sanitizer to sanitize our hand in multi public places and stores. This is our first invention to overcome the pandemic and can get easily at cheaper prices.